Female cuticular hydrocarbons can signal indirect fecundity benefits in an insect. (26th March 2019) - Berson, Jacob D.; Simmons, Leigh W.
Abstract: Male choosiness of prospective female mating partners provides an increasingly recognized pathway through which males can increase their fitness. For example, males may increase their number of offspring by targeting more fecund females as mating partners. If fecundity is heritable, males that mate with more fecund females can also receive the indirect benefit of more fecund daughters. In species where female fecundity is not directly assessable, female ornaments may act as signals of fecundity. However, whether female ornaments reliably signal the indirect benefit of more fecund daughters is not well understood. We investigated this question using the field cricket, Teleogryllus oceanicus . Previous work had identified the cuticular hydrocarbon (CHC) profile as a female sexual display trait in T. oceanicus . To examine whether CHCs can provide a reliable signal of fecundity, we tested whether individual CHC compounds and the first principal axis of CHC variation (PC1) are genetically correlated with ovary mass, a reliable proxy for fecundity in this species. We found significant genetic correlations between ovary mass and three individual CHC compounds, as well as PC1. This result indicates that by targeting females as mating partners based on their CHC profile, males can sire more fecund daughters.